Media coverage of Belgium’s first criminal case concerning euthanasia for psychiatric patients: A content analysis of Flemish newspapers and magazines - De Hert, Marc; Thys, Erik; Catthoor, Kirsten; Van den Broeck, Kris; Matthys, Frieda; Vansteelandt, Kristof; Detraux, Johan (Frontiers in Psychiatry, 2023)
BACKGROUND Belgium is one of the few countries worldwide where euthanasia on the grounds of unbearable suffering caused by a psychiatric disorder is legally possible. In April 2010 euthanasia was carried out on a 38-year-old Belgian woman with borderline personality disorder and/or autism. After a complaint by the family, three physicians were referred to the Court of Assizes on the charge of “murder by poisoning”. METHODS A content analysis of print and online news coverage of the euthanasia case in a selected sample of Flemish newspapers and magazines, published between December 1, 2019 and March 1, 2020, was conducted to analyze the prominence and framing of the euthanasia case, as well as the portrayal of key figures in this case. A quantitative analysis, as well as an in-depth qualitative analysis (with the aid of NVivo 1.0 software) was performed. RESULTS One thousand two hundred fifteen news articles were identified through database searching. Of these, 789 articles were included after screening for relevance and eligibility. Mean prominence scores were moderate and did not statistically significantly differ between newspapers with a different historical ideological background or form (elite versus popular). The most frequent headline topics featured legal aspects (relating to the Belgian Euthanasia Law or the course of the trial). Headlines and content of most articles (90% and 89%, respectively) did not contain an essential standpoint on the euthanasia case itself or, if they did, were neutral. Historical ideological background, nor form of newspaper (elite versus popular) significantly influenced headline tone or article direction toward the euthanasia case. Despite this, our qualitative analysis showed some subtle differences in selection, statement or tonality of reports between certain newspapers with a different historical ideological background. CONCLUSION Although major Flemish newspapers and magazines generally were neutral in their coverage of the judicial case, major points of contention discussed were: the need for an evaluation and possible amendments to the existing Euthanasia Law, including a revision of the Belgian Control Commission and the system of penalties for physicians, and the absence of any consensus or guidance on how to define psychological suffering.